Pengaruh Pelatihan Dan Pengembangan Karyawan Terhadap Peningkatan Kinerja Dengan Kualitas Kerja Sebagai Variabel Intervening Pada Mitsubishi PT. Suka Fajar Solok - Pramudita Destavani, Shiva (Riset Sinergi Indonesia, 2024)
Abstract. Mitsubishi PT. Suka Fajar is one of the companies engaged in the automotive sector, the company's activities are to provide services in the procurement of motor vehicles which indirectly affect national development. The purpose of this study is to find out and analyze the influence of Employee Training and Development on Performance Improvement with Work Quality as an Intervening Variable. The research method used is quantitative research. The number of samples in this study was 74 respondents and used the SEM analysis tool with SmartPLS 3. In the data collection technique in this study by distributing a questionnaire using a Likert scale. The results of the study show that directly the most dominant variable, namely training, affects the quality of work positively and significantly, this shows that if the better the training applied in an agency, the quality of employee work will increase. In addition, training has a positive and significant effect on employee performance, this shows that the better the training implemented, the better the performance of employees in the agency. The most dominant indirect influence is that training has a positive and significant effect on employee performance through work quality. If the training is implemented properly, then employee performance will increase and employees will feel more satisfied with their work, so that the level of work quality will have an impact and progress on an agency.